Innovations In Vaccine Development: A Review Of Current Strategies (The Research of Medical Science Review, 2023)
Vaccine development is at the forefront of public health initiatives and plays a central role in the prevention and control of infectious diseases. This scientific review explores recent innovations in vaccine development, highlighting current strategies that have emerged to improve effectiveness, safety and accessibility. From new platforms and adjuvants to cutting- edge delivery systems, this comprehensive analysis aims to provide a nuanced understanding of the diverse approaches used in the quest for more effective and globally applicable vaccines.Keywords: Vaccine development, vaccination, new platforms, adjuvants, delivery systems, efficacy, safety, global health, infectious diseases.